Examining Profitability: Through The Lens of Board Age Diversity in Indonesian Manufacturing Firms - Florence Melvin Tewal; Rusliyawati; Syarif M. Helmi (Golden Ratio of Auditing Research, 2026)
Further insight into the impact of company size, tax planning, and leverage towards profitability through the perspective of board age diversity. Manufacturing companies of various sub-sectors that earn positive income listed on the Indonesia Stock Exchange as per the year under research are the population used. The number of companies used as samples in this study was 23, with three years of observation (2022-2024). The study uses secondary data from their companies' official websites and the Indonesian Stock Exchange. It uses a quantitative method that uses panel data regression analysis and will conduct the Chow and Hausman tests to determine the regression analysis processed with the Eviews 12 application. The research results state that company size positively affects profitability. In line with that, tax planning has a positive effect on profitability as well. Meanwhile, leverage has a negative influence on profitability. It was also found that board age diversity moderates the correlation of company size and tax planning on profitability, so any decision-making process leads to increased profitability. However, board age diversity cannot moderate the relationship between leverage and profitability.